Reliability, availability, maintainability and supportability factors in an Arctic offshore operating environment : issues and challenges - Homlong, Eirik (University of Stavanger, Norway, 2010)
Master's thesis in Offshore technology With oil and gas production reaching its tail end on many fields on the Norwegian Continental Shelf, the industry is looking towards the Arctic to start exploration and production. It is estimated that 14% of the worlds remaining oil and natural gas reserves are found in Arctic areas, most of these offshore. The harsh Arctic conditions concerning climate, lack of infrastructure and long distances generate challenges in respect to keeping risk low and regularity high on oil and gas producing installations in this area. The research presented in this thesis highlights the challenges concerning operation and maintenance of offshore production installations in Arctic areas. Challenges to Reliability, Availability, Maintainability and Supportability (RAMS) in Arctic areas are identified. The case study conducted as a part of this study indicates that maintenance will be essential in keeping regularity high on an offshore oil and gas production facility in the Arctic. Harsh operating conditions can cause increases in failure frequencies, failure modes and failure mechanisms resulting in a need for different and more frequent preventive maintenance. Many maintenance tasks and corrective repairs can be expected to be more time consuming in the Arctic than in temperate areas. Furthermore, the economic model gives an overview of the increase in man-hours and costs when the activities are planned to be conducted in arctic areas.